2010
DOI: 10.2134/agronj2009.0368
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Manure and Fertilizer Applications on Canola Oil Content and Fatty Acid Composition

Abstract: Increasing fertilizer costs have resulted in more growers evaluating the use of alternative nutrient sources such as manure. Coincidentally, the questions about fertilizer eff ects on oil yield and oil fatty acid composition have been a concern. A 2-yr study was conducted to investigate nutrient source (fertilizer urea plus S and manure) and N level (0, 84, and 168 kg N ha -1 ) eff ects on canola seed yield, total oil content, and oil composition at East Lansing and Chatham, MI. Results indicated nutrient appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
37
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 38 publications
(57 reference statements)
8
37
0
1
Order By: Relevance
“…They also showed that the level of significance of this decrease was affected by an interaction between the N rate applied, the crop hybrid, and the location (Zheljazkov et al, 2008). However, it has also been reported that increasing the N rate results in an increase in total saturated fatty acid concentration and a decrease in linolenic acid concentration (Gao et al, 2010).The analysis of oil and fatty acid content was regarded as a function of carbohydrate equivalents (Aguirrezábal et al, 2015;Echarte et al, 2012) In the present study, the unsaturated fatty acid content of oil from sunflower seeds was significantly positively related to the N fertilizer levels. Some researchers have suggested that unsaturated fatty acids were significantly affected by environmental conditions, while saturated fatty acids are not (Kandil et al, 1990) and our results would support this.…”
Section: Correlation Among Crude Fat Content Protein and Fatty Acidmentioning
confidence: 95%
“…They also showed that the level of significance of this decrease was affected by an interaction between the N rate applied, the crop hybrid, and the location (Zheljazkov et al, 2008). However, it has also been reported that increasing the N rate results in an increase in total saturated fatty acid concentration and a decrease in linolenic acid concentration (Gao et al, 2010).The analysis of oil and fatty acid content was regarded as a function of carbohydrate equivalents (Aguirrezábal et al, 2015;Echarte et al, 2012) In the present study, the unsaturated fatty acid content of oil from sunflower seeds was significantly positively related to the N fertilizer levels. Some researchers have suggested that unsaturated fatty acids were significantly affected by environmental conditions, while saturated fatty acids are not (Kandil et al, 1990) and our results would support this.…”
Section: Correlation Among Crude Fat Content Protein and Fatty Acidmentioning
confidence: 95%
“…Rapeseed oil is ordinarily utilized in human diets on account of its great nutritional quality with a high proportion of unsaturated fatty acids and fair-minded fatty-acid composition (Rehman et al, 2013;Wang et al, 2014). After extraction, remaining rapeseed meal can be used as an organic fertilizer to the cropland or as a source of animal feed (Gao et al, 2010). The nutritional nature of these products is of prime significance, because of their immediate and circuitous effects on human health.…”
Section: Introductionmentioning
confidence: 99%
“…The main effect of nutrition management on seed quality is through its influence on seed reserves potential. In this context, it has been reported that environmental conditions and nutritional status can affect oil content and fatty acid composition in plants such as canola (Gao et al, 2014) and sweet pepper (Xu et al, 2002). Seed phosphorus (P) content plays a key role in improving seed physiological aspects Sawan et al, 2011) and seedlings metabolism White and Veneklaas, 2012).…”
Section: Introductionmentioning
confidence: 99%